(untitled) (Research, Society and Development, 2021)
Implantable devices are therapeutic options for oral rehabilitation, with several presentations available in the dental consumption market. The consumption power of health products is a little explored in the literature, particularly in the face of financial crises. The aim of this study was to evaluate the economic impact of biomaterials for bone regeneration in Brazil during the pandemic. A quantitative study was carried out through online document analysis, with publicly accessible secondary data extracted from IBGE and websites for the sale of dental products. Data collection in the second quarter of 2020 and 2021 of absolute values ​​of products, official GDP data and population estimates allowed the generation of a biomaterial/income coefficient. The categories obtained from grafts and membranes were stratified by composition, origin and industry. Statistical analysis used the Shapiro-Wilk test to assess normality, the non-parametric Kruskall-Wallis test to compare the means of variables and the Wilcoxon test for paired samples of medians according to the two periods, considering significant differences if p <0.05. Of 97 products analyzed, a higher frequency of bone grafts than barrier membranes was observed, with an average growth of 18.5% in the price of biomaterials, below 28.7% of GDP in the same period. The highest prevalence of biomaterials was the ceramic composition for bone grafts and resorbable polymeric for membranes, from the xenogenous source and Brazilian industry. There was a chronological decrease in the biomaterial/income coefficient in most categories, with a drop in the general average from 4.67±4.40% to 4.30±3.96%, accompanied by an increase in the median, demonstrating a trend towards homogeneity of this coefficient in the comparison between years. The drop in the coefficient indicates a greater purchasing power of biomaterials by the potential consumer. Market knowledge can contribute for the decision making in clinical planning involving bone regeneration.